2014
DOI: 10.15680/ijirset.2014.0309023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Geopolymer Concrete with Fly Ash and GGBS as Source Materials

Abstract: ABSTRACT:The objective of this project is to study the effect of class fly ash (FA) and ground granulated blast furnace slag (GGBS) on the mechanical properties of geopolymer concrete (GPC) at different replacement levels (FA0-GGBS100, FA25-GGBS75, FA50-GGBS50; FA75-GGBS25, FA100, GGBS0). Sodium silicate (Na 2 SiO 3 ) and sodium hydroxide (NaOH) solution have been used as alkaline activators. In the present investigation, it is proposed to study the mechanical properties viz. compressive strength, split tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Ordinary Portland cement (OPC) concrete is the most widely used construction material due to its high performance in terms of workability, compressive strength and cost [1]. However, the growing demand of OPC poses great challenges to concrete industry because of its large carbon emissions [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinary Portland cement (OPC) concrete is the most widely used construction material due to its high performance in terms of workability, compressive strength and cost [1]. However, the growing demand of OPC poses great challenges to concrete industry because of its large carbon emissions [2].…”
Section: Introductionmentioning
confidence: 99%
“…This motivates researchers for seeking suitable alternatives to OPC, and alkali-activated concrete is considered as a potential alternative by utilising industry by-products such as fly ash (FA) and ground granulated blast-furnace slag (GGBS) [3][4][5]. Although alkali-activated concrete shows comparable engineering properties as OPC concrete, critical concerns have been raised that the alkali-activated fly ash (AAF) concrete requires elevated temperature curing to improve early-age strength [1]. Whereas the alkali-activated slag (AAS) system has rapid setting time and relatively lower workability than OPC [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, PCC exhibits a negative effect on the environment due to the emission of carbon dioxide (CO 2 ) during the production of cement [20]. In comparison to PCC, geopolymer concrete (GPC) not only exhibits corresponding advantageous properties as PCC, but also higher initial strength, small drying shrinkage, high fire resistance, superior acid resistance and shorter setting time [21]. The geopolymer binder is synthesized by alkali activation of aluminosilicate materials in amorphous form, which are produced from industrial waste materials.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers utilizing MPCM have mostly utilized standard concrete recipes, which are more readily available for Portland cement. In addition, problems with short setting times of GPC [21,24], can be worsened when MPCM is added to the mixture. The comparison between Portland cement concrete and geopolymer concrete with the addition of MPCM is therefore very interesting.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of gain in compressive strength and split tensile strength of geopolymer concrete is very fast at 7 days curing period and the rate gets reduces with age. [8] A. Rajerajeswari et al (2014)has studied to reveal the possibility of silica fume based geopolymer concrete to find out its compressive strength by considering the parameters such as effect of Na 2 Sio 3 /NaOH ratio, effect of AL/SF ratio and effect of age of concrete. From the experimental investigation it was found that out of three different ratios of Na 2 Sio 3 , three different ratios of AL/SF, four different ages of silica fume based geopolymer concrete AL/SF=0.25 and Na 2 SiO 3 /NaOH=0.5 yielded better gain in compressive strength.…”
Section: Previous Research Review Based On Geo Polymer Concrete By Usmentioning
confidence: 99%